ANALISIS NOVEL GENESIS KARYA RATIH KUMALA (KAJIAN PSIKOLOGI SASTRA DAN NILAI-NILAI PENDIDIKAN KARAKTER) - Linda Eka Pradita (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2018)
A research on novel Genesis by Ratih Kumala employed a literary psychological study focusing on literary work as a mental activity (conflict of characters) requiring a holistic analysis to interpret meaning, mandate, and message contained within it. Novel Genesis by Ratih Kumala featured several conflicts affecting its characters’ personality. The conflicts featured in this novel were very complex, either inner conflict or conflict with other characters as human mentality process eventually affecting attitude and conduct. The approach used in this study was descriptive qualitative one. The data of research constituted words, sentence in the form of expression, and dialog between characters indicating the mentality conflict occurring inside the characters on which this study focused. Meanwhile the data source of research was source document, such as books of literary theory, literary psychology and novel Genesis by Ratih Kumala. The sampling technique used in this study was purposive sampling one. Technique of collecting data used in qualitative research was interactive and non-interactive in nature. This study employed theoretical, source or data, and methodological triangulations. Technique of analyzing data used in this research was an interactive analysis one encompassing data reduction, data display, and conclusion drawing and verification. The procedure of research included preparation, implementation and presentation of research result. The psychological aspect of character existing in novel Genesis by Ratih Kumala employed Sigmund Freud’s theory distinguishing personality into three types: ide, Ego, and Superego. Literary psychological research was based on these three psychological domains. In novel Genesis, the author had the reason why she featured a nun represented as capable of providing positive nuance to readers’ perception on a nun submitting her entire life to God and avoided from the author’s determination as if she wanted to confirm that every human being encountering problem in his/her life should submit to his/her fate, submit everything to God’s destiny and get closer to God. Pawestri disentangled her tension in her life by deciding to be a nun as the form of her submission to God because she could not retain burden of her past memories, the reason why she preferred living celibate.